THE ROLE OF COMMUNITY IN THE DEVELOPMENT OF WAE REBO AS A COMMUNITY-BASED TOURISM DESTINATION IN EAST NUSA TENGGARA - Beeh, Yefri Yunikson (Institut Pariwisata dan Bisnis Internasional, 2017)
Wae Rebo is an unique traditional village, known as a famous cone shape house architectures and called in Manggarai language is Mbaru Niang, it has been there since 1920. Mbaru Niang has seven building with the different name, there are Niang Gendang, Niang Gena Mandok, Niang Gena Jekong, Niang Gena Ndorom, Niang Gena Jintam, dan Niang Gena Maro. They was built in sphere around an altar with the circle shape, called Compang. The people of wae rebo consider Compang as a sacred things. Wae Rebo also has another kinds of culture like Penti ceremony and Caci dance. Not only has kinds of cultures2 but they also has rich potentials of nature like mountain range forest, and then any type of bird like Gagak Flores (Corvus florensis) and Celepuk Flores (Otus alfredi). They are known as the endemic species of Flores Island.Community Based Tourism (CBT) is a tourism concept that used in wae rebo tourism development application. CBT concept in the wae rebo tourism application from the beginning like planning, implementation, and the last is controlling doing by society. To protect the culture, people of wae rebo make a community of society organization named Lembaga Pelestari Budaya Wae Rebo and supported by social organization. The motto of that Lembaga Pelestari Budaya Wae Rebo is “Mohe Wae Rebo. Meaning of that motto is Keep Wae Rebo alive.